The use of near peer teachers in the radiography program at Monash University. Issue 3 (August 2019) - Boyd, L.; Lawson, C.; MacLeod, W.; Harianto, S.
Abstract: Introduction: This research investigated the perceptions of fourth year students as near peer (NP) teachers, and second year NP learners during a pathology unit in the Bachelor of Medical Imaging and Radiation Sciences at Monash University. Methods: A systematic review of literature was undertaken to inform the research design. Semi-structure pre- and post-teaching interviews were conducted with four NP teachers. An online survey was conducted with 50 second year NP learners. Quantitative data was analysed using Microsoft Excel. Interview data and 64 free text comments in the online survey were analysed using NVivo. Results: NP students felt there were significant benefits being involved in the NP program, including an explanation of concepts and complementary teaching to lecturers. Three of the free text comments outlined a negative perception, although in each case the comment related to the student's individual learning style rather than being negative against the program. Conclusion: The benefits to learners in a pathology course was consistent to those identified within the literature. Students perceived benefits in terms of content delivery, interaction and communication. Recommendations were made about the organisation and design for future cohorts. Highlights: Near-peer teaching can explain concepts complementary to teaching of lecturers. Near-peer students benefited in content delivery, interaction and communication. Near-peer teachers benefited by reinforcing their knowledge and building rapport. In future, near-peer teachers require preparation by students prior to class.